2017
DOI: 10.1038/ncomms15817
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic control of RhoA reveals zyxin-mediated elasticity of stress fibres

Abstract: Cytoskeletal mechanics regulates cell morphodynamics and many physiological processes. While contractility is known to be largely RhoA-dependent, the process by which localized biochemical signals are translated into cell-level responses is poorly understood. Here we combine optogenetic control of RhoA, live-cell imaging and traction force microscopy to investigate the dynamics of actomyosin-based force generation. Local activation of RhoA not only stimulates local recruitment of actin and myosin but also incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
130
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 76 publications
14
130
2
Order By: Relevance
“…Interestingly, a recent study has demonstrated that stress fibers display elastic‐like properties on time‐scales exceeding the turnover of individual constituent components (> 60 min). This elastic‐like behavior is regulated and depends on specific stress fiber proteins such as zykin (Oakes et al , 2017). Elastic effects on surprisingly long timescales have also been observed in cell monolayers (Sunyer et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study has demonstrated that stress fibers display elastic‐like properties on time‐scales exceeding the turnover of individual constituent components (> 60 min). This elastic‐like behavior is regulated and depends on specific stress fiber proteins such as zykin (Oakes et al , 2017). Elastic effects on surprisingly long timescales have also been observed in cell monolayers (Sunyer et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used flexible linkers have stretches of Gly and Ser residues, the length and copy number of which can be optimized to separate the functional domains. For LOVpep, we have successfully used the flexible linker GGSGGSGGSPR, and for tandem PDZ we have used QSTVPRARDPPVAT (Cavanaugh et al, 2020;Oakes et al, 2017;Wagner & Glotzer, 2016). Other linkers for optogenetic tags include GSGGSGSGGT (Wang & Hahn, 2016) or GSTSGSGKPGS-GEGSTKG (Whitlow et al, 1993).…”
Section: Of 19mentioning
confidence: 99%
“…[25][26][27] In support of these findings, FA proteins have been shown to be intrinsically mechanosensitive. Examples of this can be observed in the member of the mechanosensitive Cas family, p130Cas, which was shown to become extended and phosphorylated under tension, 28 zyxin which is recruited to strained areas along actin fibers, thereby regulating their elasticity, 29 talin, which was demonstrated to alter conformation as a function of force exertion, 30,31 and vinculin, which requires force to localize to FA compelxes. 25,27 Quantitative measurements using cytoskeleton laser nanosurgery also provided evidence of direct actin stress fiber association to the substrate, recruiting FA proteins such as zyxin to areas with highest tensed anchorage.…”
Section: The Cytoskeleton and Mechanosensitive Moleculesmentioning
confidence: 99%